Detection of stratospheric intrusion events and their role in ozone enhancement at a mountain background site in sub-tropical East Asia. (1st January 2022) - Ou-Yang, Chang-Feng; Babu, Saginela Ravindra; Lee, Jia-Ren; Yen, Ming-Cheng; Griffith, Stephen M.; Lin, Chia-Ching; Chang, Shuenn-Chin; Lin, Neng-Huei
Abstract: In this study, we investigated the influences of stratospheric intrusion (SI) on the tropospheric ozone (O3 ) at Lulin Atmospheric Background Station (LABS, 2862 m MSL), a representative high-altitude site in East Asia. Thresholds for surface O3, carbon monoxide (CO), and relative humidity (RH) were set to identify SI events at LABS. Accordingly, 3.0% of the observation period was impacted by SI leading to a net O3 enhancement of 14.6 ± 9.6 ppb at LABS. Factors influencing the two most common SI event types affecting LABS, i.e. tropopause folds (major) and tropical cyclones (minor), were discussed. We utilized ERA5 reanalysis products (meteorology and O3 ) to trace and analyze the pathway and mechanism of these SI types over sub-tropical East Asia. With a conceptual model, we illustrate two driving circulations for SI air at ∼200 hPa that affect subtropical East Asia. SI air generated due to Rossby wave breaks are transported equatorward and downward into the troposphere. The southern westerlies passing south of the Tibetan Plateau can further push the SI air eastward. A SI event in 2007 with a significant O3 enhancement of 43.4 ppb caused by typhoon Nari was detected and discussed to depict the second SI type. Graphical abstract: A conceptual model at ∼200 hPa presenting the two driving circulations for SI air to affect subtropical East Asia. High and low-pressure centers are indicated as H and L in the figure, respectively. Image 1 Highlights: Stratospheric intrusions identified with O3, CO, and RH measurements. A net O3 enhancement of 14.6 ± 9.6 ppb attributed to SI. Tropopause folds due to Rossby wave breaks are the major SI affecting the site. A case study of SI caused by the typhoon Nari in September 2007 was discussed.